2018
DOI: 10.3846/transport.2018.6433
|View full text |Cite
|
Sign up to set email alerts
|

Smart Grid Technologies in Electric Power Supply Systems of Public Transport

Abstract: Nowadays the issue of electric energy saving in public transport is becoming a key area of interest which is connected both with a growth in environmental awareness of the society and an increase in the prices of fuel and electricity. It can be achieved by improving the usage of regenerative breaking. In 2016 the Przedsiębiorstwo Komunikacji Trolejbusowej (PKT, Trolleybus Transport Company) in Gdynia began practical implementation of Smart Grid solutions within its trolleybus network. These activities constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…This study provides some initial insights into the transformation of public transport systems with the use of new technologies in trolleybuses and corresponds to the previous research results in e.g., ELIPTIC project [89], also for Gdynia [90]. It is a good benchmark and reference paper for similar ones, as the electromobility in urban public transport is developing very fast, becoming a promising pro-ecological way to make cities more sustainable.…”
Section: Discussionsupporting
confidence: 74%
“…This study provides some initial insights into the transformation of public transport systems with the use of new technologies in trolleybuses and corresponds to the previous research results in e.g., ELIPTIC project [89], also for Gdynia [90]. It is a good benchmark and reference paper for similar ones, as the electromobility in urban public transport is developing very fast, becoming a promising pro-ecological way to make cities more sustainable.…”
Section: Discussionsupporting
confidence: 74%
“…For instance, taxi drivers may feel tired while driving their taxis instead of feeling tired suddenly at the arrival position. Suppose that there is a subject moving from spacetime (t 1 , s 1 ) to spacetime t n , s q and that the subject's value of the specific factor c k is continuous; then, the individual value of the subject during the time period t 1 ∼ t n can be calculated by Formula (24):…”
Section: Transportation Utility Methodsmentioning
confidence: 99%
“…(iii) PT technologies. Bartlomiejczyk et al (2018) [24] introduced smart grid technologies based on the practices in Gdynia and indicated that these technologies could save electric energy for PT systems. Thomä et al (2019) [25] proposed a distributed multi-input-multi-output radar service based on 5G technology to support PT safety.…”
Section: Public Transportationmentioning
confidence: 99%
“…The main thing in the formation of intelligent technologies based on SMART Grid is the organization of all-mode computer monitoring of the entire complex of parameters of the power system as the basis for full-scale information support. The use of modern technologies of distributed vector measurements WAMS (Wide Area Measurement System) in which, thanks to the use of functionally oriented microprocessor devices PMU (Phasor Measurement Unit) and the widespread use of GPS satellite navigation systems, have opened up enormous possibilities for carrying out, with high accuracy, synchronous measurements of mode parameters in various points and segments of the distributed power system topology [5,6].…”
Section: Relevancementioning
confidence: 99%